Secondary seed dispersal by mammals between protected and grazed semiarid woodland - Miguel, María Florencia (2018)
The spatial continuity of habitats contributes to maintaining ecological processes across human-modified landscapes. Boundaries between differently managed lands may affect species interactions, such as seed dispersal, which is a key ecological process contributing to plant recruitment. We proposed a study of plant-frugivore interactions based on an experimental design of offering fruits at distance from a boundary to interior areas between protected and grazed drylands. We found that the number of visits and fruits removed differed among distance classes and among mammalian frugivores. Also, habitat cover differed across distance classes. Interactions by seed disperser species were more frequent at distances nearer boundary and from boundary toward grazed fields. Conversely, interactions by seed predator species were more frequent at distances further from boundary to both land uses. We suggest that seed dispersers may be connecting lands at different spatial scales according to species-specific differences in body size and movement capacity. Studying boundaries with a functional approach contributes to assessing the sensitivity of species to boundaries and its effect on key ecological functions between protected areas and human-managed surrounding lands.